Gene editing of the wheat homologs of TONNEAU1‐recruiting motif encoding gene affects grain shape and weight in wheat. (28th July 2019) - Wang, Wei; Pan, Qianli; Tian, Bin; He, Fei; Chen, Yueying; Bai, Guihua; Akhunova, Alina; Trick, Harold N.; Akhunov, Eduard
Summary: Grain size and weight are important components of a suite of yield‐related traits in crops. Here, we showed that the CRISPR‐Cas9 gene editing of TaGW7, a homolog of rice OsGW7 encoding a TONNEAU1‐recruiting motif (TRM) protein, affects grain shape and weight in allohexaploid wheat. By editing the TaGW7 homoeologs in the B and D genomes, we showed that mutations in either of the two or both genomes increased the grain width and weight but reduced the grain length. The effect sizes of mutations in the TaGW7 gene homoeologs coincided with the relative levels of their expression in the B and D genomes. The effects of gene editing on grain morphology and weight traits were dosage dependent with the double‐copy mutant showing larger effect than the respective single copy mutants. The TaGW7 ‐centered gene co‐expression network indicated that this gene is involved in the pathways regulating cell division and organ growth, also confirmed by the cellular co‐localization of TaGW7 with α‐ and β‐tubulin proteins, the building blocks of microtubule arrays. The analyses of exome capture data in tetraploid domesticated and wild emmer, and hexaploid wheat revealed the loss of diversity around TaGW7‐ associated with domestication selection, suggesting that TaGW7 is likely to play an important role in the evolution of yield component traits in wheat. Our study showed how integrating CRISPR‐Cas9 system with cross‐species comparison can help to uncover the function of a gene fixed in wheat for allelic variants targeted by domestication selection and select targets for engineering new gene variants for crop improvement. Significance Statement: Grain size and weight are important components of a suite of yield‐related traits in crops. We used CRISPR‐Cas9 gene editing, gene expression network and diversity analyses to demonstrate that TaGW7: (i) affects grain shape and weight in wheat through pathways regulating cell division and organ growth; (ii) was the target of domestication and improvement selection; and (iii) can be used as a target for CRISPR‐Cas9‐based mutagenesis to expand diversity available for crop improvement.